The Engagement Gap: Social Mobility and Extracurricular Participation among American Youth. Issue 1 (January 2015) - Snellman, Kaisa; Silva, Jennifer M.; Frederick, Carl B.; Putnam, Robert D.
Participation in extracurricular activities is associated with positive youth outcomes such as higher education attainment and greater future earnings. We present new analyses of four national longitudinal surveys of American high school students that reveal a sharp increase in the class gap in extracurricular involvement. Since the 1970s, upper-middle-class students have become increasingly active in school clubs and sport teams, while participation among working-class students has veered in the opposite direction. These growing gaps have emerged in the wake of rising income inequality, the introduction of "pay to play" programs, and increasing time and money investments by upper-middle-class parents in children's development. These trends need to be taken into account in any new initiative to monitor mobility. They also present a challenge to the American ideal of equal opportunity insofar as participation in organized activities shapes patterns of social mobility.